A Bibliometric Review of Online Counseling for Mental Health: A Scopus Database Study - Ali Ghozi; Sahro Wardi; Cecep Hilman; Ucu; Salsabila, Shufi (Journal of Science and Education (JSE), 2024)
This study presents a bibliometric review of online counseling and mental health, utilizing the Scopus database to analyze publication trends from 2019 to 2024. The research aims to identify key trends, influential authors, and emerging topics in the field. By analyzing 298 documents with advanced bibliometric methods, including author collaboration analysis, descriptive statistics, keyword co-occurrence analysis, and citation analysis, the study highlights a significant rise in publications after 2023, emphasizing the growing relevance of online counseling in mental health. The findings also reveal notable research surges driven by global events and technological advancements, showcasing the field's dynamic evolution. This study underscores the importance of interdisciplinary collaboration and advocates for further exploration of the effectiveness and scalability of online counseling. The insights gained offer valuable guidance for educators, policymakers, and researchers, promoting the integration of online platforms into educational and mental health frameworks